Study of Thermal Deformation Behavior of Uranium-molybdenum Alloys by Compression Experiments - HU Bingkun1, 2, LI Mingyang1, 2, HE Yabin1, 2, DU Yanhua1, 2 (Yuanzineng kexue jishu)
In order to study the thermal deformation behavior of uranium-molybdenum alloy, and to provide theoretical support for the design of uranium-molybdenum alloy press working, Gleeble3800 thermo-mechanical simulator was utilized to perform single-pass compression experiments on uranium-molybdenum alloy in the conditions of deformation temperatures of 500, 600, 700 ℃, and strain rate of 0.01, 0.1, 1 s−1. The true stress-true strain curves of uranium-molybdenum alloys were established at various temperatures and strain rates, and the effects of temperature and strain rate on the deformation stress of uranium-molybdenum alloys were analyzed. At the same time, the microstructures of uranium-molybdenum alloys were analyzed after thermal deformation, and the constitutive equations of the uranium-molybdenum alloys and the processing map were established. The results show that the true stress of uranium-molybdenum alloy increases with the true strain and then tends to be stabilized, and a dual-phase organization of α-U and Mo2Ux phases is formed in uranium-molybdenum alloy after thermal deformation. The activation energy of uranium-molybdenum alloy during thermal deformation is about 590.4 kJ/mol. The constitutive equations and the processing map of the alloy which are consistent with practice were constructed with peak stress and strain rate and temperature.